Electrocardiographic artefact mimicking arrhythmic change on the ECG. Issue 4 (1st July 2003) - Samaniego, N C; Morris, F; Brady, W J
Abstract : Artefact on electrocardiograms is a source of potential misdiagnosis and may lead to patients' receiving unnecessary treatments. This article present two cases that illustrate this problem, and will briefly look at known internal and external causes of artefact.